A pergunta como estratégia de mediação didática no ensino de matemática por meio da Sequência Fedathi - Sousa, Francisco Edisom Eugenio de (2015)
The use of the question as didactic mediation strategy in living Fedathi Sequence forms the core of the research that resulted in this thesis. Fedathi Sequence is the teaching methodology used by teachers and researchers from the Multimedia Research Laboratory of the Faculty of Education at the Federal University of Ceará, where the essence of which is shown in mediating posture of the teacher in the classroom. The question was proposed and used in this work as the foundation of a mediator teacher action classified into five types: routine, investigative, diagnostic, evaluative and counterexample. The main objective of this research summarized in to analyze the contributions of the question use mediation as a teaching strategy in teaching mathematics in initial classes of elementary school, from the experience of teaching methodology Sequence Fedathi. As theoretical contributions, the research was based on theories and works that bring approaches to the question and on their use in the teaching field, especially Fedathi Sequence, with its principles, levels and stages. The research was methodological basis the principles of qualitative research, through action research. Fieldwork was conducted in a public school elementary school in the municipal city of Quixadá-CE, having as subjects teachers this stage of education, in different number on each investigative phase. The research took place in three stages: bibliographical study; empirical research; and production of the report. The empirical research was conducted in four phases: exploratory research; continuing education; observation of teachers using the question; and analysis of the practice of these teachers. The continuing education activities consisted of face meetings; individual care; and not face meetings, using the TelEduc platform. Each teacher took the question in three educational sessions with Fedathi Sequence, at its three levels: preparation, experience and analysis, which have been reported and analyzed two lessons of each teacher. With the analysis came to the following findings and conclusions: the use of the question as didactic mediation strategy in living Fedathi Sequence provides the investigative mathematics education, where the student takes the researcher posture; the use of question requires that the teacher takes the mediator posture; the mediating posture of the teacher to use the question depends on your learning and mathematical knowledge, but also his conception of teaching and the teaching of Mathematics.